2019
DOI: 10.1016/j.carj.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Imaging-Based 3-Dimensional Printing for Improved Maxillofacial Presurgical Planning: A Single Center Case Series

Abstract: Purpose 3-D printing is an increasingly widespread technology that allows physical models to be constructed based on cross-sectional medical imaging data. We sought to develop a pipeline for production of 3-dimensional (3-D) models for presurgical planning and assess the value of these models for surgeons and patients. Methods In this institutional review board–approved, single-center case series, participating surgeons identified cases for 3-D model printing, and after obtaining patient consent, a 3-D model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Several studies have assessed how surgeons and patients view the use of 3DP in surgery. 9,10 In a study of 25 patients undergoing facial feminization, La Padula et al found that 3DP was effective and also improved overall satisfaction and patient happiness using the Satisfaction With Life Scale and Subjective Happiness Scale. 9 Reported benefits of using a 3D printed model were the ability to plan surgery and to demonstrate to patients the expected postsurgical skeletal changes.…”
Section: Surgical Planningmentioning
confidence: 99%
“…Several studies have assessed how surgeons and patients view the use of 3DP in surgery. 9,10 In a study of 25 patients undergoing facial feminization, La Padula et al found that 3DP was effective and also improved overall satisfaction and patient happiness using the Satisfaction With Life Scale and Subjective Happiness Scale. 9 Reported benefits of using a 3D printed model were the ability to plan surgery and to demonstrate to patients the expected postsurgical skeletal changes.…”
Section: Surgical Planningmentioning
confidence: 99%
“…17 The 3D printing model rebuilt by superimposing all layers of transverse CT images with bioplastic filaments has been widely applied in maxillofacial surgeries. 4 It not only offers the convenience of clarifying the complicated anatomy, 3,[17][18][19] enhancing the operation outcomes by patient-specific 3D printed plates, 20,21 but also can be used to design surgical guides in mandibuloplasty 22,23 and skull osteomas. 24 With 3D printing models, surgeons can plan the incision design, surgical approach, osteotomy plane, resection of overgrown structure, and implants inserted for soft tissue defects preoperatively, especially in unconventional or complicated cases.…”
Section: Discussionmentioning
confidence: 99%
“…24 With 3D printing models, surgeons can plan the incision design, surgical approach, osteotomy plane, resection of overgrown structure, and implants inserted for soft tissue defects preoperatively, especially in unconventional or complicated cases. 18 Never-theless, one of the major challenges in traditional maxillofacial surgery is the evaluation of the distance from the infraorbital rim to the optic canal, where the optic nerve is located. When repairing orbital blowout fractures, limited surgical space, frequent instrument manipulation, and multiple attempts to adjust the implant placement may make the optic nerve and vessels vulnerable to compression and damage 25,26 and consequently compromise the functional and cosmetic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…3-dimensional models have been shown to improve patient surgical consent by increasing patient understanding of anatomy and surgery compared to traditional consent processess. 6,9 The models were used in conjunction with translators to aid in communication of the plan to patients prior to surgery. The consent process is challenging in this setting due to the need for translation and the use of models helped to produce higher confidence for the surgical team that the patients had an improved understanding of the plan.…”
Section: Discussionmentioning
confidence: 99%
“…The value of using 3-dimensional (3D) printing to plan surgery, specifically in maxillofacial reconstruction, is to reduce operative time and increase both patient and surgeon confidence in the procedure. [2][3][4][5][6][7] The use of prebent plates in mandibular reconstruction using patient-specific 3D modeling techniques has been reported to significantly decrease operative time and improve accuracy of the reconstruction. 8 It was recognized that time savings, while valuable in a highresourced setting, could be even more valuable in a lowresourced setting, such as Haiti, where operating time and supplies are very limited.…”
Section: Introductionmentioning
confidence: 99%